EVALUASI PENERAPAN E-KATALOG TERHADAP PENGADAAN BARANG DAN JASA DI SEKRETARIAT DAERAH KABUPATEN BUTON - Ratna; Mahyudin; La Asiri (Halu Oleo University, 2025)
This study aims to evaluate the implementation of the e-catalogue system in the procurement of goods and services at the Secretariat of Buton Regency. The identified issue is the effectiveness of the e-catalogue system in accelerating the procurement process and the challenges faced during its implementation. This research employs a descriptive approach with a qualitative method, where data were collected through interviews with ten respondents involved in the procurement process. The findings indicate that the e-catalogue system accelerates the process of searching for goods and suppliers, but there are challenges in budget management, unstable internet connection, and underutilization of advanced system features. Manual procedures in transaction approval also hinder efficiency. Overall, while the e-catalogue has improved efficiency in searching for goods, improvements in technology infrastructure, user training, and simplification of administrative procedures are needed to achieve greater effectiveness. This research contributes to the development of the e-catalog system in government procurement.